Chronic administration of caffeine alters acesulfame-K intake and features of fungiform taste buds in mice. (17th November 2021) - Lu, Jiali; Mao, Yuezhong; Qi, Jiaming; Han, Jianzhong; Qin, Yumei
Abstract: The objective of this study was to investigate the effects of chronic administration of caffeine on the anatomical characteristics of taste buds, the expression level of taste receptor protein in mice, and preference for a palatable solution. We found that following a 21-day administration of caffeine, mice showed increased behavioural responses to sweet stimuli (acesulfame-K solution). Mirroring this behavioural change, chronic caffeine treatment evidently decreased the maximal cross-sectional area and height of the longitudinal axis of fungiform taste buds, the number of taste cells per fungiform taste bud, and the expression of G protein α-gustducin, while the expression of the sweet taste receptors T1R2 and T1R3 was reversed. Our findings demonstrate that chronic administration of caffeine has an impact on taste sensitivity and changes in taste bud features, which may contribute to the alteration of taste behaviour.